High Endogenous Testosterone Levels Are Associated With Diminished Neural Emotional Control in Aggressive Police Recruits. (August 2019) - Kaldewaij, Reinoud; Koch, Saskia B. J.; Zhang, Wei; Hashemi, Mahur M.; Klumpers, Floris; Roelofs, Karin
Although police officers are carefully selected for their high emotion-regulation abilities, excessive aggression in police officers has been reported, particularly in socially challenging situations known to elicit high state testosterone levels. Adequate regulation of emotional actions depends on the prefrontal cortex's control over the amygdala. We investigated the effects of trait aggression and endogenous testosterone on this emotional-control neurocircuitry in 275 healthy, high-functioning police recruits using a functional MRI social-emotional task eliciting impulsive and controlled approach-and-avoidance actions. Higher levels of aggression were counteracted by increased anterior prefrontal cortex (aPFC) control over the amygdala when control over automatic emotional actions was required. Crucially, testosterone had a detrimental effect on this aggression-dependent aPFC recruitment: Police recruits with relatively high trait aggression and high state testosterone showed reduced aPFC control over the amygdala during emotion regulation. This provides a mechanistic explanation for inadequate behavioral control during socially challenging situations in otherwise well-functioning individuals.